The development of narrative writing ability among ESL students in a Sarawak secondary school / Gepat Gedip - Gedip, Gepat (2012)
Narrative writing is a difficult ESL classroom task in Malaysia, especially among Sarawakian students. Many language teachers, however, assume that students are well versed and creative in producing desired writing, because it is personal experience based. A good piece of narrative writing should portray the right point of view, the proper use of dialogue, tagging, organization pattern and text organization. All of these characteristics require the appropriate and relevant use of AOQ (adjectives of quality) and AOM (adverbs of manner) in producing an interesting and lively narrative writing. Due to the importance of these two word classes, they have become the focus of the analysis of students' narrative writing ability development. This study aims to investigate the development of 203 randomly selected ESL students' narrative writing ability. The writing exercise uses prescribed picture series as writing stimuli to find out the students' syntactic maturity in the use of AOQ and AOM, and complexity of sentences in their writing at three age levels (namely, Form One, Form Two and Form Four), using the T-unit index, namely, the total number of T-units and the mean T-unit lengths (1977). The respondents were required to write an essay within sixty minutes. To examine the students' development of narrative writing, the total number of T-units, the mean T-unit length and the use of AOM (adverb of manner) and AOQ (adjective of quality) were identified manually and analysed using SPSS. The results showed that there was a strong correlation between the total number of AOQ and the mean T-unit length used in the narrative writing at the three different age groups. This shows that as the use of AOQ increases in the narrative writing, the sentence becomes more complex. On the contrary, there was no statistical difference among the three different age groups with regards to the mean T-unit length and the use of AOM. At individual levels, there were indications that some students showed a gradual increase in the use of AOM. The study concluded that there was a positive development in the students' ability in narrative writing based on the T-unit index and the use of AOQ and AOM.